Uncovering suicide risk factors: a qualitative study in Malaysia - Mohd Munir, Nur Syuhada; Rais, Haniza; Zubairi, Ainol Madziah (ASIAN SCHOLAR NETWORK, 2025)
This study aims to explore the risk factors experienced by individuals with suicidal behaviours in Malaysia from the perspectives of survivors with lived experience and counsellors. Previous research primarily focuses on descriptive data and perceptions related to suicidal behavioural experiences, with limited studies examining risk factors from the viewpoint of those with firsthand experience. Using a qualitative case study approach, this study involved four individuals with incomplete suicidal experiences and ten counsellors working in various institutions, including schools, correctional facilities, private practices, colleges, and others. Participants were recruited through purposive sampling, and data were collected via semi-structured interviews. Thematic analysis was used to analyse the gathered data and derive meaningful themes that reflected the study. The emergent themes that illustrated this issue include the multifaceted risk factors associated with suicidal tendencies: (1) psychological factors, (2) social factors, (3) family factors, (4) medical conditions, (5) physiological responses, (6) variation of external factors, (7) social media and technology involvement and (8) socio-cultural spiritual factors. Understanding these risk factors highlights key contributors to suicidal behaviours. The findings can assist counselling professionals in better understanding the suicidal crisis during sessions and enhance intervention strategies to address urgent psychological cases linked to suicidality. This study advocates for broader initiatives in suicide prevention research in Malaysia, involving diverse sectors such as individuals, society, institutions, communities, and legislative bodies.